2017
DOI: 10.18632/oncotarget.20139
|View full text |Cite
|
Sign up to set email alerts
|

[10]-gingerol induces apoptosis and inhibits metastatic dissemination of triple negative breast cancer in vivo

Abstract: There is increasing interest in the use of non-toxic natural products for the treatment of various pathologies, including cancer. In particular, biologically active constituents of the ginger oleoresin (Zingiber officinale Roscoe) have been shown to mediate anti-tumour activity and to contribute to the anti-inflammatory, antioxidant, antimicrobial, and antiemetic properties of ginger. Here we report on the inhibitory properties of [10]-gingerol against metastatic triple negative breast cancer (TNBC) in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 37 publications
(43 reference statements)
1
40
0
Order By: Relevance
“…Gingerol is a major phenolic compound present in the rhizomes of ginger (Z. officinale Roscoe). In a syngenic mouse model of spontaneous breast cancer metastasis, gingerol (5 mg/ kg) treatment induced caspase-3 activation and inhibited the orthotopic tumor growth as well as metastasis of mouse brainmetastatic 4T1Br4 mammary tumor cells to multiple organs such as lung, bone and brain (Martin et al, 2017). Likewise, Joo and colleagues (Joo et al, 2016) reported inhibition of lungmetastatic, MDA-MB-231 human breast cancer cell proliferation, and invasion by [10]-gingerol through suppression of Akt, p38MAPK, and epidermal growth factor receptor.…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…Gingerol is a major phenolic compound present in the rhizomes of ginger (Z. officinale Roscoe). In a syngenic mouse model of spontaneous breast cancer metastasis, gingerol (5 mg/ kg) treatment induced caspase-3 activation and inhibited the orthotopic tumor growth as well as metastasis of mouse brainmetastatic 4T1Br4 mammary tumor cells to multiple organs such as lung, bone and brain (Martin et al, 2017). Likewise, Joo and colleagues (Joo et al, 2016) reported inhibition of lungmetastatic, MDA-MB-231 human breast cancer cell proliferation, and invasion by [10]-gingerol through suppression of Akt, p38MAPK, and epidermal growth factor receptor.…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…To verify whether the complex (2) is able to arrest cell cycle, propidium iodide (PI) staining was performed, as described earlier [27]. MDA-MB-231 and MCF-10A cells were seeded (5 × 10 5 /1000 μL) in appropriate culture medium into 6 cm Petri dishes and maintained at 37°C in a humidified incubator with 5% CO 2 for 24 h. After, cells were treated or not (control) with different concentrations of the complex (2) (0.5, 1 and 2 μM) for 24 h and maintained under the same conditions described above.…”
Section: Cell Cyclementioning
confidence: 99%
“…The organs were harvested, photographed, fixed in 10% buffered formalin for 24 h and processed for histology. Tumour growth and spontaneous metastasis assays were completed as described previously [34,42]. For these assays, fluorescent mCherry-tagged TBCP-1 cells (1 × 10 6 /20 μl PBS) were inoculated into the fourth mammary fat pad and tumour growth measured thrice weekly with electronic callipers.…”
Section: Tumour Growth Metastasis Assays and Neratinib Therapymentioning
confidence: 99%
“…The incidence of mice with brain metastases at endpoint was determined by ex vivo fluorescence imaging using a Maestro™ In-Vivo Imaging System (CRi) and, where indicated, further confirmed by histology and cytokeratin staining (see below). Relative metastatic burden in the lungs, femurs and spine of the control and treatment groups was quantitated by genomic qPCR detection of the mCherry marker gene present in tumour cells only, relative to the vimentin gene present in tumour and host cells, as described previously [34,37,42].…”
Section: Tumour Growth Metastasis Assays and Neratinib Therapymentioning
confidence: 99%